Analysis Quality Public Services: The Creation Number of Identification Business (NIB) in Pacitan Regency - Annshori, Muhammad Faqih; Senatama, Gandung (Indo-MathEdu Intellectuals Journal, 2026)
The provision of effective public services is an important indicator of government performance, particularly in business licensing administration. This study aims to analyze the quality of public services in the issuance of NIB at the DPMPTSP of Pacitan Regency. This study uses a quantitative approach using questionnaire data collected from 40 respondents who processed NIB services from November 7 to November 15, 2024. The sampling technique uses non-probability sampling through accidental and quota sampling methods. The data were analyzed using Importance-Performance Analysis (IPA) to examine the gap between perceived service performance and importance levels across five service quality dimensions: reliability, responsiveness, empathy, assurance, and tangibles. The research results indicate that the overall quality of NIB services at the DPMPTSP of Pacitan Regency is categorized as good, with an average performance score of 4.175 and an importance score of 4.725 on a five-point scale. IPA quadrant analysis shows that most indicators fall into Quadrant B, indicating that service performance meets public expectations. However, one indicator in the reliability dimension still needs improvement. These findings suggest that although the overall service quality is satisfactory, enhancing staff readiness and providing service information are necessary to improve the effectiveness of public services.